Exploring Possibilities of Public Private Partnership for Leptospirosis Control Programme in South Gujarat - Rutu S. Buch; Bansari L Chawada; Vipul P Chaudhari; J K Kosambiya (Medsci Publications, 2019)
Introduction: Leptospirosis is seasonal epidemic in South Gujarat and having high case fatality rate since 1994 within young productive tribal population. Private practitioners are nearest available for consultation to these workers. The study was conducted to assess the knowledge, practice, felt need for training and to explore the possibilities of public private partnership to control Leptospirosis in south Gujarat region. Material and Methods: A cross sectional study was carried out by using pre-designed and pre-tested semi-structured questionnaire during September 2013. Private practitioners practicing at Kamrej and Mahuva block of south Gujarat were contacted. Descriptive analysis was done to analyse the data. Observation: Out of 45 private practitioners contacted, 5 were Post Graduates, 39 were Graduates, and 1 was unqualified. Among them, 14 were Allopathic, 16 Ayurvedic, 14 Homeopathic. Most of the practitioners (97.83%) heard of Leptospirosis. More than half (53.33%) of the practitioners were not having knowledge of causes of Leptospirosis, 26.67 % were having correct knowledge while around 20 % were having partial knowledge of causes of Leptospirosis. Conclusion: This study envisioned the possibility of partnership with private practitioners. Basic training can help to sensitize private practitioners towards Leptospirosis control activity.